THE APPLICATION OF RESTORATIVE JUSTICE IN MINOR HEALTH LAW OFFENCE CASES - Shohib Muslim; Karman (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The application of restorative justice in health law misdemeanour cases presents a more humanist and recovery-oriented alternative approach to the traditional justice system. It emphasises dialogue and conflict resolution through cooperation between perpetrators, victims and communities, in order to reach mutually beneficial solutions. Restorative justice in the context of health law aims to repair relationships, increase understanding, and promote improvements in the quality of health services. While offering many potential benefits, the application of this concept faces significant challenges such as a lack of understanding and awareness and the need for clear regulations. Therefore, the successful implementation of restorative justice relies heavily on synergistic support from the government, health institutions, professional organisations, and the community in creating a conducive environment and providing adequate education and training.